Pathological Assessment of Men with Grade Group 2 Prostate Cancer - Anika Jain; Lawrence Kim; Manish I. Patel (The World Journal of Men's Health)
Purpose: A variety of treatment options are now available for men with localized prostate cancer (PC); however, there is still debate in determining how and when to intervene for Grade Group (GG) 2 disease. Our study aims to formulate strategies to identify men at risk of upgrading and having adverse pathological outcomes. Materials and Methods: This retrospective study includes 243 patients with GG2 PC that were treated with radical prostatectomy between 2015 and 2021. Patients on active surveillance, previous history of prostate biopsy, hormonal and/or radiation therapy prior to surgery were excluded from this study. A retrospective analysis was conducted using clinicopathological data obtained from medical records. Results: Prostate-specific antigen (PSA) and Prostate Imaging Reporting and Data System (PI-RADS) score were statistically significant variables for risk of upgrading. In men who had presence of composite poor outcomes, PSA, PI-RADS score, presence of extraprostatic extension and seminal vesical invasion on MRI, number of positive cores, percentage of high grade (pattern 4/5) on prostate biopsy and Gleason pattern 4 volume on biopsy were all statistically significant variables. Strategy 8 (PI-RADS 5 lesion or percentage high grade [Gleason pattern 4] on prostate biopsy grade >10% or >3 cores positive on prostate biopsy) had significant association to identifying the highest number of men with upgrading and composite poor outcomes. Conclusions: Our study supports the use of strategy 8 in treatment decision making of men with GG2 PC. Further validation of the use of this strategy is warranted.